Partographic analysis of labour by modified WHO partograph in tertiary care centre - Jain, Prekshi; Shah, Akshay C.; Patel, Babulal S.; Jani, Shashwat K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The partograph is a simple, inexpensive tool to provide a continuous pictorial overview of labor. The goal of this study is to use partograph to monitor labor, initiate uterine activity that is sufficient to produce cervical changes, fetal descent while avoiding uterine hyperstimulation, hypostimulation and fetal distress and provide timely surgical intervention where required. Methods: A hospital-based observational study involving prospective review of partographs for births that occurred in 2020 was conducted in 2 hospitals including SVP Hospital and V.S hospital Ahmedabad. A partographic analysis of labour was done in randomly selected 200 patients using modified WHO partogram. The study population was divided into Primigravida (96) and Multigravida (104) term patients. partograph recording were commenced at 4 cm dilatation. close maternal and fetal monitoring was done throughout the labour and partogram was plotted to detect any deviation from normal course. Results: Patients were grouped into primigravida and multigravida and based on partogram finding divided into mode of delivery. 22 of total 96 primigravida underwent caesarean section and 74 delivered vaginally. 8 of total 104 multigravida underwent caesarean section and 96 delivered vaginally. Out of 200 newborn only 11 had Apgar score <7 at 5 minutes. Conclusion: The WHO modified partograph is highly effective in reducing both maternal and neonatal morbidity. It aids in assessing the progress of labour and to identify when intervention is necessary. It is effective in preventing prolonged labour, obstructed labour, reducing operative intervention and improving neonatal outcome.